The Impact of Service Quality Factors on Inpatient Satisfaction at Ibnu Sina Hospital in 2023 - Salam, Fajrin Moelyawan; Waspodo, Nurelly Noro; Ningsih, Iin Widya; Kartika, Andi Visi; Yanti, Kartini Eka (Formosa Journal of Science and Technology, 2024)
Hospitals play a strategic role in accelerating the improvement of public health standards. Health services require hospitals to provide high-quality care while adhering to medical and professional codes of ethics. Every individual has the right to receive quality, safe, and affordable healthcare. Based on the above, the research problem statement is: How do service quality factors affect inpatient satisfaction at Ibnu Sina Hospital in 2023? A descriptive analysis using a cross-sectional approach. The research method employed is quantitative, with data collected through questionnaires. Patient services are excellent, and the alignment between inpatient expectations and the quality of healthcare services is very high, resulting in patient satisfaction with the services provided at Ibnu Sina Hospital in 2023.